Estimation of the total, fork and precaudal lengths for the silky shark, Carcharhinus falciformis (Carcharhiniformes: Carcharhinidae), from the interdorsal length - Santana-Hernández, Heriberto; Tovar-Ávila, Javier; Valdéz-Flores, Juan Javier (HIDROBIOLÓGICA, 2016)
The suitability of using the interdorsal length (IL) to estimate total (TL), fork (FL) and precaudal (PL) lengths of Carcharhinus falciformis in the Central Mexican Pacific (CMP) was analyzed. A linear model described adequately the relationships (TL = 3.974IL + 8.277, FL = 3.297IL + 6.561 and PL = 3.016IL + 4.814, r = 0.99 and p < 0.001 in all cases, n = 1196, 1162 and 1164 respectively). No significant differences between sexes were found for all the relationships (ANCOVA, p > 0.05 for all cases), but significant differences were found with both TL and PL estimated from IL with equations previously reported for the species in the South Eastern Pacific Ocean (t = -161.58, d.f. = 1199, p < 0.001 and t = -228.522, d.f. = 1168, p < 0.001 respectively). Such differences could be related to the short dimensions of IL, as discrepancies appeared to be larger in small organisms. Thus, measuring IL with the highest possible accuracy is recommended. IL is an alternative easy-to-take measure that allows estimation of sharks size when landed as carcass. The use of the present equations for C. falciformis from the CMP is recommended to standardize measurement methods, thereby allowing more reliable population comparisons based on shark size.